Experimental and theoretical analysis of TiO2 powders flow properties at ambient and high temperatures. (10th August 2017) - Macrì, Domenico; Barletta, Diego; Lettieri, Paola; Poletto, Massimo
Highlights: Temperature effect on bulk flow properties of TiO2 powders is evaluated experimentally. Measured properties are related to the microscopic IPFs by theoretical models. A sensitivity analysis on models' parameters is performed. Abstract: Changes of bulk flow properties of two different types of titanium dioxide powders are measured at room temperature and 500 °C using the High Temperature Annular Shear Cell. A significant increase of the macroscopic bulk flow properties is observed with increasing temperature, in particular with regards to the unconfined yield strength. Two different modelling approaches are proposed with the aim to relate the measured properties to the microscopic interactions between particles. The results indicate that both the model provides a good match with the experimental data when proper values for the models' parameters are taken into account. To this end, the sensitivity analysis for the main parameters of the models is performed.